The legal status of online loan service in Indonesia according to the Islamic jurisprudence of Shafi’i school - Singgih Muheramtohadi (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
Purpose – Start-up business has developed significantly in the last decade. The development follows the digital technology ownership. Online loan service (pinjaman online; pinjol) is one of the start-up products based on the online credit. But it has problems relating to human rights violations and Islamic Jurisprudence. This study aims to investigate the possibility of violence of online loan service (pinjol) and the view of Islamic jurisprudence of Shafi’i school on online loan service.Method – This paper uses description and analysis methods.Result – The result of this study is that one of the problem sources is the high amount of bank interest in online loan. Moreover, the debt terms are so easy, and the disbursement process is so fast, so that it causes bad credit among debtors. According to Shafi’i scholars, the high bank interest is part of the mudha’afah usury, although both parties have agreed the contract. However, the sanctions for bad debtors are not accordance with Islamic sharia that prioritize the debt (qardh) to help other people. In addition, this credit business causes so many harms (mudharat). Implication – This study will help government, business player, and consumers to understand online loan service according to Islamic jurisprudence.Originality – This study is among few other studies who investigate the current trend of online loan service in Indonesia.